The Concept of Human Security in the Case of Refugees and Asylum Seekers Caused by the World Climate Crisis - Eva Firsha*; Darmansjah Djumala; Affabile Rifawan (Riwayat: Educational Journal of History and Humanities, 2023)
The climate change crisis is not only seen as a threat to environmental security, but also a type of human security threat that every country now focuses on. The insecurity brought by the climate crisis has already forced millions of people to flee their countries as it adversely affects their living conditions, bringing about the term 'climate refugee'. However, the use of this term is still unclear regarding the status of refugees and asylum seekers who are victimized by the climate change crisis and need international protection. This research aims to analyze how the climate crisis can affect and create insecurity for refugees and asylum seekers by adding the concept of human security. This research also uses qualitative research methods analyzed with use of Atlas.ti as a qualitative analysis tool. The results show that refugees and asylum seekers affected by the global climate crisis become the multiple victims of the threat of human security caused by environmental and human rights protection factors.